Comparison of effectiveness and safety of camrelizumab between HBV-related and non-B, non-C hepatocellular carcinoma: A retrospective study in China - Haonan Liu; Xiaobing Qin; Zhiyuan Xu; Meng Wu; Tong Lu; Shuang Zhou; Nan Yao; Suya Liu; Yong Shao; Zhengxiang Han (Frontiers in Genetics, 2022)
Purpose: This study aimed to compare the clinical outcomes of camrelizumab in hepatitis B virus-related hepatocellular carcinoma (HBV–HCC) patients and non-HBV, non-HCV hepatocellular carcinoma (NBNC–HCC) patients in China.Materials and methods: A total of 54 patients with hepatocellular carcinoma who received camrelizumab were included in this retrospective study from January 2019 to December 2021. The patients were assigned to the HBV–HCC group (n = 28) and the NBNC–HCC group (n = 26). The primary endpoints were overall survival (OS) and progression-free survival (PFS), and the secondary endpoints were the objective response rate (ORR), disease control rate (DCR), and adverse events (AEs). Multivariate analysis using Cox proportional hazard regression was used to identify independent prognostic factors. A nomogram model was subsequently established based on independent prognostic factors.Results: The mean duration of follow-up was 12.7 ± 3.6 months. The median OS was not determined. The median PFS in the HBV–HCC group was significantly longer than that in the NBNC–HCC group (9.2 vs. 6.7 months, p = 0.003). The ORR and DCR in the HBV–HCC group were significantly higher than those in the NBNC–HCC group (ORR, 28.6% vs. 7.7%, p = 0.048; DCR, 71.4% vs. 42.3%, p = 0.031). No significant differences in the total incidence of AEs were found between the HBV–HCC group and the NBNC–HCC group (75.0% vs. 69.2%, p = 0.224). Multivariate regression analysis identified etiology, AFP level, and vascular invasion as independent prognostic factors (all p < 0.05).Conclusion: Our findings demonstrate that camrelizumab is more effective in HBV–HCC patients than in NBNC–HCC patients, with manageable safety.